Peran Kearifan Lokal Bagi Pengembangan Pendidikan Karakter Pada Sekolah Menengah Atas - M. Rizqon Al Musafiri (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2016)
The purpose of this study to determine the role of local knowledge for the development of character education at the high school. The design of this research is descriptive quantitative. This study describes the local wisdom and a few examples that can be developed as an educational character. This research involves several aspects such as the values contained in the character education and integrated with local knowledge through examples of local wisdom that can be developed as learning. The collection of data through observation, interviews, and library. Langkah-step application of character development in schools can take to reduce the impact of juvenile delinquency through several stages of the study, co-curricular activities and extracurricular, alternative development and character building in schools as an actualization of school culture, as well as daily activities at home and in the community